2018
DOI: 10.1007/s10265-018-1024-y
|View full text |Cite
|
Sign up to set email alerts
|

A global comparison of the nutritive values of forage plants grown in contrasting environments

Abstract: Forage plants are valuable because they maintain wild and domesticated herbivores, and sustain the delivery of meat, milk and other commodities. Forage plants contain different quantities of fibre, lignin, minerals and protein, and vary in the proportion of their tissue that can be digested by herbivores. These nutritive components are important determinants of consumer growth rates, reproductive success and behaviour. A dataset was compiled to quantify variation in forage plant nutritive values within- and be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
126
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 80 publications
(95 reference statements)
18
126
0
12
Order By: Relevance
“…Crude protein concentration followed the seasonal pattern of greater CP concentration in the winter and lower in the spring [45,46]. Previous studies comparing perennial ryegrass found CP concentrations of between 60-61 and 340-353 g kg −1 DM, with a mean of 180-229 g kg −1 DM [47,48].…”
Section: Discussionmentioning
confidence: 68%
“…Crude protein concentration followed the seasonal pattern of greater CP concentration in the winter and lower in the spring [45,46]. Previous studies comparing perennial ryegrass found CP concentrations of between 60-61 and 340-353 g kg −1 DM, with a mean of 180-229 g kg −1 DM [47,48].…”
Section: Discussionmentioning
confidence: 68%
“…Secondly, NDF, ADF and lignin are less edible fiber components than the non-fibrous constituent as crude protein. In forage, there are inverse relationships between digestibility with fiber and crude protein; as the fiber content of forage increases, its digestibility decreases, but as the crude protein increases, the forage digestibility increases (Lee 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides water availability, the temperature is an essential factor that influences the nutritive value of forages (Buxton and Fales 1994). Commonly, tropical grasses from warmed environments have a lower digestibility associated with higher fiber and lower protein contents compared to temperate grasses from cooler and wetter regions (Lee 2018). Overall, an increase in temperature stimulates plant growth but decreases leaf:stem ratios and increases NDF, ADF and lignin contents (Lee et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They extend across tropical and temperate regions, but the quality of the forage differs between them. Temperate pastures are, in general, considered to be of high quality, due to the higher digestibility and lower fiber content of temperate compared with tropical species [8]. The most commonly-cultivated pastures include grasses (e.g., Agrostis spp., Festuca spp., Lolium spp., and Dactylis spp.)…”
Section: Introductionmentioning
confidence: 99%